Effect of Different Levels of Protein in Total Mixed Ration on Growth Performance, Digestibility and Microbial Protein Production in Vechur Cattle - Thampi, Gopika; RANI, K. JASMINE; Ally, K.; Bunglavan, Surej Joseph; Kurian, Elizabeth; Vyshnav, B. (Indian Journal of Animal Nutrition, 2025)
ABSTRACT The effect of different levels of protein in total mixed ration was evaluated based on the growth performance, digestibility, and microbial protein production in Vechur cattle. Fifteen Vechur cattle of six to ten months of age were randomly assigned to one of the three treatments. T1 - Total mixed ration containing 16 % CP and 60% TDN, T2 - Total mixed ration containing 14% CP and 60% TDN, and T3 - Total mixed ration containing 12 % CP and 60% TDN. The results indicated that total dry matter intake (DMI), fortnightly average dry matter intake, total body weight gain, average daily gain (ADG), and feed conversion efficiency (FCE) were similar (P > 0.05) among the three treatment groups. No variations were observed for the apparent digestibility of nutrients. The purine derivatives excretion, urinary creatinine excretion, microbial protein production, the duodenal flow of microbial nitrogen, PDC index, and the efficiency of microbial nitrogen production showed no significant (P > 0.05) distinction among the dietary treatments. Therefore, it could be resolved that Vechur cattle can be reared on TMR containing 12% CP and 60% TDN without any negative effects on the animals’ health and provide a profit.